High-graphite-adhesion mixed solid material and preparation method thereof

By designing a mixed solid material with high graphite adhesiveness in powder metallurgy conduits, using the combination of graphite free state and alloy elements, the problem of difficult to take into account both the compression performance and lubricity of the conduit is solved, and the high compression strength and wear resistance of the conduit are achieved.

CN119794330APending Publication Date: 2025-04-11CHONGQING ZHIBO POWDER METALLURGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411991192.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When manufacturing conduits with existing powder metallurgy technology, carbon penetration into the substrate is difficult to control, resulting in low compression performance of the conduit, and it is difficult to adjust the graphite particle size to take into account the lubricity and wear resistance of the conduit.

Method used

Design a highly graphite adhesive mixed solid material. By adjusting the sintering process parameters of graphite, it forms a free state, increasing the self-lubricating effect of the conduit, and adding alloy elements such as molybdenum, copper, phosphorus, tin and other alloy elements and rare earth elements are added to avoid segregation and flying with adhesives.

Benefits of technology

Improves the compressive strength, lubricity and wear resistance of the catheter, ensuring stability and performance when used under high temperature and dry friction conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of powder metallurgy parts and preparation methods thereof, and discloses a high-graphite-adhesion mixed solid material and a preparation method thereof, and the high-graphite-adhesion mixed solid material is prepared from the following chemical raw materials in percentage by mass: 1.7-3% of graphite, 0.1-0.5% of molybdenum, 3-6% of copper, 0.1-0.5% of phosphorus, 0.1-0.7% of tin, 0.3-0.5% of rare earth elements and the balance of an adhesive. According to the invention, 1.7-3.0% of graphite is used, and 1-2% of graphite is sintered to form a free state by adjusting sintering process parameters, so that the self-lubricating effect of the solid material is improved. Meanwhile, the solid material contains alloy elements such as molybdenum, copper, phosphorus, tin and the like and is modified by rare earth elements, so that the solid material can normally work at the temperature of 950 DEG C or below and can be used under the working conditions of high temperature, dry friction and sulfur-containing atmosphere, and when the solid material is applied to the natural gas engine, normal work of the natural gas engine can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder metallurgy parts and preparation methods thereof, and in particular to a mixed solid material with high graphite adhesion and a preparation method thereof. Background Art

[0002] The guide tube is a guide device for the automobile engine valve. It guides the valve and transfers the heat on the valve stem to the cylinder head through the guide tube.

[0003] The existing use of powder metallurgy technology to manufacture catheters has the problem that the carbon infiltration into the matrix is ​​difficult to control, and network cementite is easily generated due to improper control, resulting in low crushing performance of the catheter. Therefore, in the prior art, the carbon content of the powder metallurgy catheter is around eutectoid, and the excessive cementite produced by the eutectoid increases its brittleness and reduces its performance; however, in order to prevent excessive carbon from infiltrating into the matrix, the graphite particle size used is too large and the sintering temperature is too low, which will increase the weakening effect on the matrix strength and cause the catheter to have insufficient wear resistance; however, if the graphite particle size used is too small and too fine, it is easy to produce segregation and flying during the mixing and feeding process.

[0004] Therefore, in order to solve the above technical problems, the inventors designed a high graphite adhesion mixed solid material and a preparation method thereof, which can sinter graphite to form a free state, increase the lubrication effect of the catheter, and use the adhesive added during the mixing process to avoid segregation and flying. Summary of the invention

[0005] The present invention aims to provide a mixed solid material with high graphite adhesion and a preparation method thereof, which can sinter graphite to form a free state, increase the lubrication effect of the catheter, and use the adhesive added in the mixing process to avoid segregation and flying.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] 1) A high graphite adhesive mixed solid material, comprising the following chemical raw materials in the following mass percentages: 1.7-3% graphite, 0.1-0.5% molybdenum, 3-6% copper, 0.1-0.5% phosphorus, 0.1-0.7% tin and 0.3-0.5% rare earth element, and the balance is adhesive.

[0008] The graphite ingredient in the present invention is 1.7-3.0%, and by adjusting the sintering process parameters, 1-2% of the graphite is sintered to form a free state, thereby increasing the self-lubricating effect of the solid material. At the same time, the present invention contains alloy elements such as molybdenum, copper, phosphorus, and tin, and is modified with rare earth elements, so that the solid material can work normally below 950°C and be used under high temperature, dry friction and sulfur-containing atmosphere conditions. The solid material is applied to natural gas engines to ensure the normal operation of natural gas engines.

[0009] In the present invention, the purpose of adding molybdenum is to form molybdenum carbide with a relatively high melting point and hardness, good thermal stability and mechanical stability, and excellent corrosion resistance, so as to improve the high-temperature hardness, strength, thermal fatigue resistance, and corrosion resistance of solid materials. In addition, molybdenum has a large affinity for oxygen and can form MoO2, MoO3, MoO3-x(0<x<1), etc. Due to its unique physical and chemical properties, it has strong mechanical and thermal stability.

[0010] The main role of phosphorus in the alloy is to improve the high-temperature strength, thermal fatigue resistance, high-temperature sulfur corrosion resistance, and oxidation resistance. Phosphorus can be uniformly doped into the molybdenum carbide (MoC) structure in the form of phosphomolybdenum bonds to form phosphorus-doped molybdenum carbide nanowires. This doping can significantly improve the electrocatalytic hydrogen production activity and stability of the catalyst, so as to improve the high-temperature resistance, thermal fatigue resistance, corrosion resistance, and oxidation resistance of fixed materials. Tin can significantly improve the mechanical properties, corrosion resistance, and oxidation resistance, and can interact with phosphorus, molybdenum, etc. to further improve the corrosion resistance, high-temperature oxidation resistance, and thermal strength of solid materials.

[0011] 2) A high-graphite adhesiveness hybrid solid material according to 1), wherein:

[0012] The graphite is 1.7%, molybdenum is 0.1%, copper is 3%, phosphorus is 0.1%, tin is 0.1%, and rare earth elements are 0.3%, and the balance is the adhesive.

[0013] Based on graphite and copper, the present invention is formulated with the element ratios of molybdenum, phosphorus, and tin, not only reasonably distributing the strength and hardness of the solid material, but also establishing a coherent C-Cu high-efficiency heat conduction channel, achieving a two-way enhancement of heat conduction and wear resistance of the solid material.

[0014] 3) A high-graphite adhesiveness hybrid solid material according to 1), wherein:

[0015] The graphite is 2.5%, molybdenum is 0.5%, copper is 5%, phosphorus is 0.5%, tin is 0.5%, and rare earth elements are 0.4%, and the balance is the adhesive.

[0016] In the present invention, molybdenum, phosphorus, and tin maintain a consistent ratio and are matched with the ratios of graphite and copper. Under the action of the adhesive, molybdenum, phosphorus, and tin respectively undergo matching chemical reactions and physical reactions with graphite and copper, enabling the solid material to have good strength and hardness, while also ensuring the lubricity of the solid material.

[0017] 4) A high-graphite adhesiveness hybrid solid material according to 1), wherein:

[0018] The graphite is 3%, molybdenum is 0.3%, copper is 6%, phosphorus is 0.3%, tin is 0.7%, and rare earth elements are 0.5%, and the balance is the adhesive.

[0019] The conduit made of solid material in this scheme is used for working near the combustion chamber end. However, due to the high working temperature near the combustion chamber end, the effect of oil storage lubrication is limited. Therefore, in order to solve the above technical problems, the inventor designed a special value of graphite of 3%, and regulated the graphite of 3% to contact with copper of 6%, which greatly improved the oil storage lubrication effect of the solid material. After high-temperature sintering of the conduit using this material, the hardness and wear resistance of the conduit are improved, and the lubricity and processability of the conduit are improved, which meets the requirements of the conduit of the National VI displacement of the engine and below.

[0020] 5) A high graphite adhesion mixed solid material according to 1), wherein:

[0021] The rare earth element includes any one or two of cerium, lanthanum and yttrium.

[0022] The rare earth elements cerium, lanthanum and yttrium in the present invention are highly active and easily combined with oxygen, sulfur and other elements to form rare earth oxygen-sulfur compounds RE2O2S and the like, which can simultaneously play the role of deoxidation and desulfurization, reducing the adverse effects of sulfur and oxygen on the catheter at high temperatures; one of the main forms of damage to the catheter at high temperatures is preferential oxidation of grain boundaries, and trace amounts of rare earth elements can effectively inhibit this damage. Rare earth is a surface active element, has a greater affinity with oxygen, and is conducive to the formation of a denser rare earth compound, such as SnO2, which can promote the formation of a surface oxide reaction film during the friction process, thereby helping to reduce adhesion between friction pairs, reduce wear, and improve wear resistance.

[0023] Rare earth can form stable compounds with high melting points, become extremely tiny heterogeneous crystal nuclei, and play a role in refining grains; rare earth also hinders the migration of grain boundaries during sintering, can significantly refine grains, and provide more diffusion channels for alloy elements, which is conducive to obtaining uniform and dense sintered bodies. Rare earth also reduces sintering power, promotes spheroidization and shrinkage of pores in sintered bodies, makes particle rearrangement more favorable, and thus significantly changes the pore morphology and distribution, making the pores tend to spheroidize and homogenize; rare earth also has the function of microalloy strengthening; improves the morphology, size and distribution of harmful inclusions; refines and rounds carbides; rare earth elements can also purify and strengthen grain boundaries, hinder the initiation and growth of intergranular cracks, and can significantly improve the toughness, plasticity, wear resistance, corrosion resistance and high temperature strength of the catheter.

[0024] 6) A high graphite adhesion mixed solid material according to 1), wherein:

[0025] The copper is electrolytic copper powder.

[0026] The copper in the present invention is electrolytic copper powder. The added electrolytic copper powder contains multi-element copper, which can effectively fill the porosity in the catheter, so that the catheter produces a more favorable inner wall capillary structure layer, and also increases the density of the catheter and its heat conduction. At the same time, on this basis, the added adhesive can prevent the electrolytic copper powder from agglomerating during the manufacturing process and improve the strength of the catheter.

[0027] 7) A method for preparing a mixed solid material with high graphite adhesion, which is applied to any one of the mixed solid materials with high graphite adhesion described in the above schemes 1) to 6), comprising the following steps:

[0028] Step 1: Separate molybdenum, copper, phosphorus, tin and rare earth elements into two base materials, mix the first base material with graphite of a matching ratio, add a portion of adhesive during the mixing process and mix for 20-35 minutes to obtain a first mixture;

[0029] Step 2: The remaining molybdenum, copper, phosphorus, tin and rare earth elements are used as the second base material, and the second base material is mixed with the remaining adhesive for 30-60 minutes to obtain a second mixture;

[0030] Step 3: Mix the first mixed material obtained in step 1 and the second mixed material obtained in step 2, and sinter them at 150-220° C. to obtain a solid material.

[0031] 8) A method for preparing a mixed solid material with high graphite adhesion according to 7), wherein:

[0032] During the mixing process in step 1, the finished powders of graphite, molybdenum, copper, phosphorus, tin and rare earth elements have flowability of ≤45s / 50g and a loose density of 2.7-3.5g / cm.

[0033] 9) A method for preparing a mixed solid material with high graphite adhesion according to 7), wherein:

[0034] During the mixing process in step 2, the finished powders of molybdenum, copper, phosphorus, tin and rare earth elements have flowability of ≤45s / 50g and a loose density of 2.7-3.5g / cm.

[0035] 10) A method for preparing a mixed solid material with high graphite adhesion according to 7), wherein:

[0036] In step three, during the sintering process, the protective atmosphere for sintering is 90% N2+10% H2, and the sintering time is 30-60 minutes.

[0037] Compared with the prior art, the present invention also has the following technical effects:

[0038] Compared with the prior art, the present invention divides molybdenum, copper, phosphorus, tin and rare earth elements into two base materials in order to ensure that graphite forms a free state during the sintering process. The first base material and the graphite ingredients are matched in a ratio of 1.7-3.0%, and they are mixed with each other under the action of a binder. At the same time, the sintering temperature is combined to ensure that the graphite is in a free state, so as to avoid the carbon content of the powder metallurgy catheter in the prior art being around eutectoid, and the eutectoid produces too much cementite, which increases its brittleness and reduces its performance, thereby improving the crushing strength of the catheter. At the same time, the first base material and the second base material are sintered at 150-220° C. to obtain a solid material, and the surface binder is volatilized by baking at a certain temperature, so that the powder material has better fluidity. DETAILED DESCRIPTION

[0039] The following is further described in detail through specific implementation methods:

[0040] Example 1

[0041] A mixed solid material with high graphite adhesion, comprising 1.7% graphite, 0.1% molybdenum, 3% copper (preferably electrolytic copper powder), 0.1% phosphorus, 0.1% tin and 0.3% rare earth element, and the balance is adhesive. The rare earth elements include cerium, lanthanum, yttrium, cerium and lanthanum, cerium and yttrium, yttrium and lanthanum, and any one of the above can be used.

[0042] Example 2

[0043] A mixed solid material with high graphite adhesion, comprising 2.5% graphite, 0.5% molybdenum, 5% copper (preferably electrolytic copper powder), 0.5% phosphorus, 0.5% tin and 0.4% rare earth element, and the balance is adhesive. The rare earth elements include cerium, lanthanum, yttrium, cerium and lanthanum, cerium and yttrium, yttrium and lanthanum, and any one of the above can be used.

[0044] Example 3

[0045] A mixed solid material with high graphite adhesion, comprising 3% graphite, 0.3% molybdenum, 6% copper (preferably electrolytic copper powder), 0.3% phosphorus, 0.7% tin and 0.5% rare earth element, and the balance is adhesive. The rare earth elements include cerium, lanthanum, yttrium, cerium and lanthanum, cerium and yttrium, yttrium and lanthanum, and any one of the above can be used.

[0046] The method for preparing a mixed solid material with high graphite adhesion in the above-mentioned embodiments 1 to 3 comprises the following steps:

[0047] Step 1, dividing molybdenum, copper, phosphorus, tin and rare earth elements into two parts of base materials, wherein the finished powder flowability of graphite, molybdenum, copper, phosphorus, tin and rare earth elements is ≤45s / 50g, and the loose density is 2.7-3.5g / cm, the first part of the base material is mixed with a matching ratio of graphite, and a part of the adhesive is added during the mixing process and mixed for 20-35min to obtain a first mixture;

[0048] Step 2: The remaining molybdenum, copper, phosphorus, tin and rare earth elements are used as the second base material, wherein the finished powder flowability of the molybdenum, copper, phosphorus, tin and rare earth elements is ≤45s / 50g and the loose density is 2.7-3.5g / cm3, and the second base material is mixed with the remaining adhesive for 30-60min to obtain a second mixture;

[0049] Step three, mix the first mixture obtained in step one and the second mixture obtained in step two, and sinter them at 150-220° C., the protective atmosphere for sintering is 90% N2+10% H2, and the sintering time is 30-60 min to obtain a solid material.

[0050] Comparison of test results:

[0051] In the test, the iron-copper bonded alloy powder was used as the solid material of comparative example 1 to compare with examples 1 to 3: high temperature wear resistance tests were conducted on a valve guide wear tester at 300°C. Compared with the conventional 200°C test condition, the use of 300°C test temperature is to more accurately simulate the high temperature working conditions of a natural gas engine. After the test was continued at the above temperature and the speed was 2000 rpm for 10 hours, the wear of the valve guide was measured as shown in Table 1 below:

[0052] Thermal conductivity W / (mK) Valve guide wear mm Tracheal wear mm Total wear mm Example 1 75 0.021 0.005 0.026 Example 2 74.5 0.024 0.006 0.03 Example 3 73.9 0.019 0.004 0.023 Comparative Example 1 58 0.098 0.020 0.118

[0053] According to the data in Table 1, the thermal conductivity and wear of Examples 1 to 3 are compared with those of Comparative Example 1. The temperature rise of Comparative Example 1 leads to performance degradation and even thermal failure. Since Comparative Example 1 does not contain graphite, its thermal conductivity is low and the wear amount is large, so it cannot be used in practical applications. Therefore, compared with the prior art, the solid material prepared by the process of the present invention has an advantage in wear resistance, which is conducive to the application in new engines such as natural gas engines, and its generally high thermal conductivity is conducive to heat dissipation and reducing the working temperature of the valve guide.

[0054] The above are only embodiments of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution are not described in detail here. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the technical solution of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A mixed solid material with high graphite adhesion, characterized in that: The adhesive is made of the following chemical raw materials in the following mass percentages: 1.7-3% graphite, 0.1-0.5% molybdenum, 3-6% copper, 0.1-0.5% phosphorus, 0.1-0.7% tin and 0.3-0.5% rare earth element, and the remainder is adhesive.

2. The high graphite adhesion mixed solid material according to claim 1, characterized in that: The graphite comprises 1.7%, molybdenum 0.1%, copper 3%, phosphorus 0.1%, tin 0.1% and rare earth element 0.3%, and the balance is adhesive.

3. The high graphite adhesion mixed solid material according to claim 1, characterized in that: The graphite comprises 2.5%, molybdenum 0.5%, copper 5%, phosphorus 0.5%, tin 0.5% and rare earth element 0.4%, and the balance is adhesive.

4. The high graphite adhesion mixed solid material according to claim 1, characterized in that: The graphite comprises 3%, molybdenum comprises 0.3%, copper comprises 6%, phosphorus comprises 0.3%, tin comprises 0.7% and rare earth elements comprise 0.5%, and the remainder is adhesive.

5. The high graphite adhesion mixed solid material according to claim 1, characterized in that: The rare earth element includes any one or two of cerium, lanthanum and yttrium.

6. The high graphite adhesion mixed solid material according to claim 5, characterized in that: The copper is electrolytic copper powder.

7. A method for preparing a mixed solid material with high graphite adhesion, according to any one of claims 1 to 6, comprising the following steps: Step 1: Separate molybdenum, copper, phosphorus, tin and rare earth elements into two base materials, mix the first base material with graphite of a matching ratio, add a portion of adhesive during the mixing process and mix for 20-35 minutes to obtain a first mixture; Step 2: The remaining molybdenum, copper, phosphorus, tin and rare earth elements are used as the second base material, and the second base material is mixed with the remaining adhesive for 30-60 minutes to obtain a second mixture; Step 3: Mix the first mixed material obtained in step 1 and the second mixed material obtained in step 2, and sinter them at 150-220° C. to obtain a solid material.

8. The method for preparing a mixed solid material with high graphite adhesion according to claim 7, characterized in that: During the mixing process in step 1, the finished powders of graphite, molybdenum, copper, phosphorus, tin and rare earth elements have flowability of ≤45s / 50g and a bulk density of 2.7-3.5g / cm.

9. The method for preparing a mixed solid material with high graphite adhesion according to claim 7, characterized in that: During the mixing process in step 2, the finished powders of molybdenum, copper, phosphorus, tin and rare earth elements have flowability of ≤45s / 50g and a loose density of 2.7-3.5g / cm.

10. The method for preparing a mixed solid material with high graphite adhesion according to claim 7, characterized in that: In step three, during the sintering process, the protective atmosphere for sintering is 90% N2+10% H2, and the sintering time is 30-60 minutes.